The Frontiers of Functionalized Nanocellulose-Based Composites and Their Application as Chemical Sensors - Norrrahim, Mohd Nor Faiz; Knight, Victor Feizal; Nurazzi, Norizan Mohd; Jenol, Mohd Azwan; Misenan, Muhammad Syukri Mohamad; Janudin, Nurjahirah; Kasim, Noor Azilah Mohd; Shukor, Muhammad Faizan A.; Ilyas, Rushdan Ahmad; Asyraf, Muhammad Rizal Muhammad; Naveen, Jesuarockiam (MDPI, 2022)
Chemical sensors are a rapidly developing technology that has received much attention in diverse industries such as military, medicine, environmental surveillance, automotive power and mobility, food manufacturing, infrastructure construction, product packaging and many more. The mass production of low-cost devices and components for use as chemical sensors is a major driving force for improvements in each of these industries. Recently, studies have found that using renewable and eco-friendly materials would be advantageous for both manufacturers and consumers. Thus, nanotechnology has led to the investigation of nanocellulose, an emerging and desirable bio-material for use as a chemical sensor. The inherent properties of nanocellulose, its high tensile strength, large specific surface area and good porous structure have many advantages in its use as a composite material for chemical sensors, intended to decrease response time by minimizing barriers to mass transport between an analyte and the immobilized indicator in the sensor. Besides which, the piezoelectric effect from aligned fibers in nanocellulose composites is beneficial for application in chemical sensors. Therefore, this review presents a discussion on recent progress and achievements made in the area of nanocellulose composites for chemical sensing applications. Important aspects regarding the preparation of nanocellulose composites using different functionalization with other compounds are also critically discussed in this review.
Keywords: nanocellulose; composites; chemical sensors; functionalization; CARBON NANOTUBES; GAS SENSORS; SUPERHEATED STEAM; CELLULOSE; GRAPHENE; NANOMATERIALS; NANOCOMPOSITES; NANOPARTICLES; PRETREATMENT; NANOFIBERS; Polymer Science